The Correlation of Parenting Styles toward Dental Caries in Toddlers - Laelia Dwi Anggraini; Octafita Agasa (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2024)
The prevalence of caries shows a percentage of 90% in toddlers in Indonesia. Caries has a negative impact on the body development of toddlers. Through the right parenting style, it is considered to be possible to reduce the caries rate in children under five. This study aims to determine the effect of parenting style on toddler dental caries in Baki District, Sukoharjo Regency. Accordingly, this analytical observational research applied a cross-sectional approach. Samples were taken using a purposive sampling technique involving 111 toddlers and their parents in Baki District. Toddler dental caries was measured using the dmft index, and parenting style was measured by a questionnaire adapted and modified from The Parenting Styles and Dimensions Questionnaire (PSDQ). Process data with IBM SPSS version 20. Results show that the parenting style of most parents involved in this study was authoritative (47,7%), followed by authoritarian (28,8%), and lastly permissive (23,4%). The highest dmft index is found in toddlers raised by permissive parents (7,92). The average education level of mothers in the three parenting styles was at the high school level (65%). The majority of parents' income in a month is in the moderate category. The conclusion showed that parenting style had no effect on toddler dental caries in Baki District, Sukoharjo Regency.